Prevalencia de Hiposalivación y su relación con la calidad de vida de los pacientes con enfermedad Renal Crónica terminal de la Unidad de Hemodiálisis del Hospital Isidro Ayora de la ciudad de Loja en el periodo marzo a julio del 2015. - Valencia Lapo, Jheyson Adrian (2015)
The study descriptive, cross sectional and experimental whose objective was to determine the prevalence of Hyposalivation and its relation to the quality of life for patients with Chronic Kidney Disease Terminal of the Unit of Hemodialysis of the Hospital Isidro Ayora in the city of Loja in the period March to July 2015; we examined 62 patients , the sample was obtained through a dry mouth questionnaire and inventory of xerostomia ; the salivary flow was measured at rest and stimulated by testing sialometry and finally was applied the questionnaire of quality of life related to xerostomia, that allowed to know the quality of life in the functional scope , pain , personal and social of patients. The results were that the prevalence of hyposalivation was 16 % with salivary flow at rest and 34 % with stimulated salivary flow. The Hyposalivation influences the quality of life of patients with hemodialysis affecting their physical functions as difficulties of Talking, altered taste of food , trouble chewing and pain, concerns about the state of their teeth , it is interfering with their daily activities ; These shortcomings were were more noticeable in some patients while others others passed by unnoticed. Most patients with dry mouth feeling said they would feel terrible and clearly dissatisfied if they had to spend the rest of their lives with that feeling. Keywords: prevalence, hyposalivation, chronic renal disease, quality of life.